Optimization of the Use of Transaction Processing Systems in Minimarkets - ., Yuhelmi; Trianita, Mery; Dharma, Surya; Sri Mulatsih, Listiana; Fitri, Rahma (KnE Social Sciences, 2020)
The use of information technology in supporting the effectiveness of company operations is very important. This study aims to determine the optimization of the use of Transaction Processing Systems in minimarkets in the city of Padang. Sampling uses accidental sampling of the owner/manager and operator in the Minimarket. The analytical method used in this study is a descriptive analysis. The results showed that 85.6% of 97 minimarkets in Padang had used transaction processing systems in support of sales activities and services to consumers. The use of computer-based transaction processing systems had resulted in shopping receipts to reduce the level of error in calculating shopping values. Information about prices and changes made by updating the database and changing labels on the product manually. Limited cooperation with banks is only 49% of minimarket providing payment facilities by debit/credit card. An interesting finding from this study is that there is a gap between the use of transaction processing systems for sales and inventory. Only 8% of minimarkets obtain information on the amount of inventory through a transaction processing system. The ordering of goods, only 10% are planned through the information system. This gap will affect the minimarket financial reports. For making this report only 14.4% of the minimarkets were able to obtain this information from the system. From the overall analysis, it can be concluded that the level of utilization of information systems for operational effectiveness is still relatively low. Keywords: Transaction Processing System, Sales, Inventory, Financial Report